From Banking to Sovereign Stress : Implications For Public Debt. (Policy Papers; Policy Paper ;, 2014)
This paper explores how banking sector developments and characteristics influence the propagation of risks from the banking sector to sovereign debt, including how they affect the extent of fiscal costs of banking crises when those occur. It then proposes practices and policies for the fiscal authorities to help manage the risks and enhance crisis preparedness.